2012
DOI: 10.1038/nmat3383
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal organic charge-transfer interfaces probed using Schottky-gated heterostructures

Abstract: Organic semiconductors based on small conjugated molecules generally behave as insulators when undoped, but the heterointerfaces of two such materials can show electrical conductivity as large as in a metal. Although charge transfer is commonly invoked to explain the phenomenon, the details of the process and the nature of the interfacial charge carriers remain largely unexplored. Here we use Schottky-gated heterostructures to probe the conducting layer at the interface between rubrene and PDIF-CN(2) single cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 36 publications
4
76
0
Order By: Relevance
“…This can be observed in recent examples of crystal on crystal lamination. Conjugating tetramethyltetraselenafulvalene and TCNQ crystals, for instance, forms a small-gap semiconductor system 34 , whereas in PDIF-CN 2 (N,N 0 -1H,1H-perfluorobutyl dicyanoperylenecarboxydiimide) and rubrene system the valence band of the electron donor (rubrene) and the conduction band of the electron acceptor (PDIF-CN 2 ) are practically aligned 35 . As a result, the interfacial electron density presents a linear dependence of the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This can be observed in recent examples of crystal on crystal lamination. Conjugating tetramethyltetraselenafulvalene and TCNQ crystals, for instance, forms a small-gap semiconductor system 34 , whereas in PDIF-CN 2 (N,N 0 -1H,1H-perfluorobutyl dicyanoperylenecarboxydiimide) and rubrene system the valence band of the electron donor (rubrene) and the conduction band of the electron acceptor (PDIF-CN 2 ) are practically aligned 35 . As a result, the interfacial electron density presents a linear dependence of the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For these devices, a junction with a large energy barrier provides rectifi cation, leading to a diode behavior, whereas a relatively small energy barrier provides a highly conductive nonrectifying behavior, resulting in efficient carrier injection into (or extraction from) the molecular semiconductor. [ 4 ] Typically, a specifi c metal/molecular semiconductor combination leads to a fi xed energy barrier, which crucially determines the device performance and effi ciency; [8][9][10] therefore, the possibility of a gate-controlled energy barrier is very appealing from the point of view of possible advanced applications.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Alves et al [38] and Gutierrez et al [39] showed that charge-transfer states formed at the interface of two bulk organic crystals could be exploited for device applications. We believe the concept developed here will be able to realize more versatile structures such as planar, vertical heterostructures and quantum wells.…”
mentioning
confidence: 99%